Posterior, predictive, and utility-based approaches to testing the arbitrage pricing theory - McCulloch, Robert; Rossi, Peter E. (Journal of Financial Economics, 1990)
To provide a framework for judging the economic significance of departures from the arbitrage pricing theory, we adopt a utility-based metric based on optimal portfolio choices. This measure is examined using both predictive and posterior analysis. Our predictive analysis shows very large and economically significant departures from the model restrictions. However, the high level of parameter uncertainty suggests that we cannot conclusively either affirm or reject the APT. Our conclusions differ markedly from other studies which employ traditional significance-testing procedures and, in many instances, fail to reject the APT restrictions.